Kearifan Lokal dalam Sastra Lisan Biak Numfor - Sri Yono Sri Yono (Balai Bahasa Provinsi Papua, 2019)
Customary heritages and values are implicitly and explicitly kept in cultural expressions as in oral tradition. Papua has multiethnic and cultures so it needs specific threaten. Local authonomy with its implication will bring impacts on many sectors. This paper aims to analys the culture value of oral tradition from Biak. Indeed, the local indegenious to be the focus. Sustainable development of Biak will be successfully if there is sufficient attention toward customary or indegenious heritages and their values. This is a library research, and the paper presented descriptively. From this oral tradition of Biak, there are some local indegenious such as concept of social, economy, culture, and technology found on it.